From Jihad to Politics: How Syrian Jihadis Embraced Politics - Drevon, Jerome (Oxford University Press, 2025)
The Syrian regime unleashed unprecedented violence to suppress large-scale non-violent protests amid the Arab uprisings. Hundreds of armed groups formed throughout the country to defend the protesters and fight back. However, in contrast to other conflicts previously dominated by al-Qaeda and Islamic State, the two largest Syrian Jihadi groups, Ahrar al-Sham and then Jabhat al-Nusra, rejected global jihad and began to cultivate new ties with the population, other armed opposition groups, and even foreign states. This strategic shift is a response to the Jihadi paradox--a realization that while Jihadis excel at leading insurgencies, they fail to achieve political victories. In From Jihad to Politics, Jerome Drevon offers an examination of the Syrian armed opposition, tracing the emergence of Jihadi groups in the conflict, their dominance, and their political transformation. Drawing upon field research and interviews with Syrian insurgents in northwestern Syria and Turkey, Drevon demonstrates how the context of a local conflict can shape armed groups' behavior in unexpected ways. Further, he marshals unique evidence from the Arab world's most intense conflict to explain why the trajectory of the transnational Jihadi movement has altered course in recent years.